Sport supplements and the athlete`s gut: A review - Wilson, P. (International Journal of Sports Medicine, 2022)
Vigorous or prolonged exercise poses a challenge to gastrointestinal system functioning and is associated with digestive symptoms. This narrative review addresses 1) the potential of dietary supplements to enhance gut function and reduce exercise-associated gastrointestinal symptoms and 2) strategies for reducing gastrointestinal-related side effects resulting from popular sports supplements. Several supplements, including probiotics, glutamine, and bovine colostrum, have been shown to reduce markers of gastrointestinal damage and permeability with exercise. Yet the clinical ramifications of these findings are uncertain, as improvements in symptoms have not been consistently observed. Among these supplements, probiotics modestly reduced exercise-associated gastrointestinal symptoms in a few studies, suggesting they are the most evidenced-based choice for athletes looking to manage such symptoms through supplementation. Carbohydrate, caffeine, and sodium bicarbonate are evidence-based supplements that can trigger gastrointestinal symptoms. Using glucose-fructose mixtures is beneficial when carbohydrate ingestion is high (>50 g/h) during exercise, and undertaking multiple gut training sessions prior to competition may also be helpful. Approaches for preventing caffeine-induced gastrointestinal disturbances include using low-to-moderate doses (<500 mg) and avoiding/minimizing exacerbating factors (stress, anxiety, other stimulants, fasting). Adverse gastrointestinal effects of sodium bicarbonate can be avoided by using enteric-coated formulations, low doses (0.2 g/kg), or multi-day loading protocols.